The impacts of quality on cervical cytopathological exams, in a triple border city, in the COVID-19 (Research, Society and Development, 2022)
The periodic performance of quality cytopathological exams in currently the way used word wide in the screening of cervical cancer (CCU), however during the COVID-19 pandemic the exams were suspended, giving priority to urgencies and emergencies in the units of health care. Objective: Evaluate the quality of cervical cytopathological exams in triple-border municipality in Paraná, through the indicators recommended by the Ministry of Health, comparing them between the periods before and during the COVID-19 pandemic. Method: Quantitative study, based on the cancer information system, of the results of 106.029 cervical cytopathologic exams of women residing in the municipality of Foz do Iguaçu-PR, from January 2014 to October 2021, through the internal quality monitoring analysis. Results: The percentage of unsatisfactory exams was 1,6%, the JEC ranged from de 36,5% to 89,3%, and the total number of exams performed during the COVID-19 pandemic ranged from 26% to 40%. The total number of exams with altered results was 3.377, with an IP% variation reaching more than six and a half time, from 1,0% to 6,5%, and HSIL% varied six times, from 0,2% to 1,2%. Conclusion: During the COVID-19 pandemic, our study showed a greater number of altered exams, and a preponderance of in situ and invasive carcinomas and adenocarcinomas. These data can help local managers in strategies for an adequate follow-up and treatment of these women with precursor lesions and/or cervical cancer.